Extended supply and use tables for Belgium: Where do we stand? - Bernhard Michel; Caroline Hambÿe; Bart Hertveldt; Guy Trachez (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2019)
The construction of extended supply and use and input-output tables has been presented as a means of addressing some of the current challenges for the national accounts that are induced by economic globalisation. Such tables take into account within-industry firm heterogeneity that is not related to product characteristics, through a disaggregation of industries by size, ownership, exporter status or other relevant criteria. Beyond their contribution to improving national accounts data, these extended tables also allow us to derive new results on the participation of categories of firms in domestic and global value chains. In this article, we give an overview of where we stand today in terms of the construction of extended supply and use and input-output tables (SUT and IOT) for Belgium: methodological choices, data used, tables that have already been constructed, and analytical results. This is designed as an input for organising future work on extended tables for Belgium, but it may also provide useful information for other countries that engage in the construction of extended SUT and IOT.
Keywords: C67; C81; D57; F14; F23; 330; economic globalisation; extended supply and use tables; input-output tables; firm heterogeneity; exporters; ownership; firm size